Forestry Action Plan for Latin America and the Caribbean : executive summary (FAO, 2011)
A forestry action plan to improve land use practices and generate income opportunities. Bases plan on five related areas of action viz forestry in land use; forest-based industrial development; fuelwood and energy conservation; and, forestry institutions.
Keywords: FORESTRY DEVELOPMENT; FOREST CONSERVATION; LAND USE; LATIN AMERICA; CARIBBEAN; REPORTS